Language Problem Solving in Children and Its Relationship to Reading Skills and Neuropsycholinguistic Disorders - Silalahi, Maysarah; Rosmawaty, Rosmawaty (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
The research entitled "Language Problem Solving in Children and Its Relationship to Reading Skills and Neuropsycholinguistic Disorders" aims to find out whether there is a relationship between language problem solving in children and children's reading skills and neuropsycholinguistic disorders. This research focuses on language problems, reading skills, and neuropsycholinguistic disorders in children. This research was conducted using descriptive qualitative methods, this method aims to describe systematically, actual and accurately. Data analysis was carried out by observation, interviews, and then recording as a data collection technique. The subjects of this research were children aged 7 to 10 years who experienced neuropsycholinguistic disorders and delays in reading and speaking. The results of the research show that language problem solving in children is related to their reading skills and neuropsycholinguistic disorders.